The using of coping strategies by students (gender aspect) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article analyzes the problem of using coping strategies bystudents of different sexes. The concepts of coping and coping-strategiesare considered. Copying behavior strategies were defined as certain waysof behaving in difficult (or stressful) situations. The diagnostic results ofcoping strategies in youth are given. The research results of stress reactionmethods are presented. The difference between the results of the researchbetween children is demonstrated: students prefer to find the right solutionsand try to apply adequate and effective coping strategies. Psychological andpedagogical methods of forming the right coping strategy for overcoming. students’ life difficulties are proposed.
Keywords: coping; coping strategies; students; strategies in youth; gender differences